Both light and soil moisture affect the rhizosphere microecology in two oak species - Lian, Jinshuo; Cai, Keke; Yin, Aijing; Yuan, Yuan; Zhang, Xinna; Xu, Chengyang (Frontiers in Microbiology, 2025)
Understanding the mechanisms by which seedlings respond to light and water regulation, as well as studying the response of rhizosphere microecology to drought stress, are crucial for forest ecosystem management and ecological restoration. To elucidate the response of the rhizosphere microecology of Quercus dentata and Quercus variabilis seedlings to water and light conditions, and to clarify how plants modulate the structure and function of rhizosphere microbial communities under drought stress, we conducted 12 water-light gradient control experiments. These experiments aimed to offer scientific theoretical support for the dynamic changes in rhizosphere soil enzyme activities and microbial community compositions of these two oak species under varying light and moisture conditions, and subsequently assist in the future breeding and cultivation efforts. The results are summarized as follows: (1) The activities of cellulase, urease, and chitinase in the rhizosphere soil of Q. dentata and Q. variabilis were significantly influenced by water and light treatments (p < 0.05). Urease was particularly sensitive to light, while sucrase exhibited sensitivity to light in Q. dentata and no significant difference in Q. variabilis. (2) Compared to Q. dentata, the rhizosphere bacteria of Q. variabilis demonstrated greater adaptability to drought conditions. Significant differences were observed in the composition of microorganisms and types of fungi in the rhizosphere soil of the two Quercus seedlings. The fungal community is significantly influenced by light and moisture, and appropriate shading treatment can increase the species diversity of fungi; (3) Under different water and light treatments, the rhizosphere soil microbial composition and dominant species differed significantly between the two Quercus seedlings. For instance, Streptomyces, Mesorhizobium, and Paecilomyces exhibited significant variations under different treatment conditions. Specifically, under L3W0 (25% light, 75–85% moisture) conditions, Hyphomonadaceae and SWB02 dominated in the Q. dentata rhizosphere, whereas Burkholderiales and Nitrosomonadaceae were prevalent in the Q. variabilis rhizosphere. Overall, the rhizosphere microecology of Q. dentata and Q. variabilis exhibited markedly distinct responses to varying light and water regimen conditions. Under identical conditions, however, the enzyme activity and microbial community composition in the rhizosphere soil of these two oak seedlings were found to be similar.